Penyuluhan Informasi Konseling Kesehatan Kepada Orang Tua Melalui Media Video Interaktif - Hasna Fadhilah; Muhamad Rifa’i Subkhi (Pakis Journal Institute, 2024)
The use of interactive video media in health education for students is becoming a more relevant topic in the health sector. This article examines the benefits, drawbacks, and effectiveness of using interactive video technology to convey health information to the elderly. Through the use of a combination of striking visuals, more refined interactive features, and broader accessibility, interactive video can improve learning, motivation, and retention of Health-related information. The research methods used included in-depth literature searches, surveys, and interviews with health workers and information technology experts. The results of the research in this study are that the use of interactive video media in health education for the elderly has been proven to be an effective and promising approach in increasing understanding, motivation and retention of health information.